2014
DOI: 10.1038/srep05264
|View full text |Cite
|
Sign up to set email alerts
|

A meta-substrate to enhance the bandwidth of metamaterials

Abstract: We propose the concept of a meta-substrate to broaden the bandwidth of left-handed metamaterials. The meta-substrate, which behaves like an inhomogeneous magnetic substrate, is composed of another kind of magnetic metamaterials like metallic closed rings. When conventional metamaterial rings are printed on this kind of meta-substrate in a proper way, the interaction of the metamaterials units can be greatly enhanced, yielding an increased bandwidth of negative permeability. An equivalent circuit analytical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Air matrix was chosen in this study to get the real part of e r close to 1 that is the necessary condition for using Eqs. (1)(2)(3)(4)(5) in this case. In fact, the real part of e r cannot be equal to 1 for any real two-component metal-dielectric composite.…”
Section: Antenna Miniaturization Problemmentioning
confidence: 82%
See 3 more Smart Citations
“…Air matrix was chosen in this study to get the real part of e r close to 1 that is the necessary condition for using Eqs. (1)(2)(3)(4)(5) in this case. In fact, the real part of e r cannot be equal to 1 for any real two-component metal-dielectric composite.…”
Section: Antenna Miniaturization Problemmentioning
confidence: 82%
“…In this case, using Eqs. (4), (5), and (7) finally gives: L magn 5 0.000453 v and W magn 5 0.0347 v. Free space FDTD simulations for the magnetic metamaterial substrates have shown that Iron cylinders must be partially magnetized in such a way that the relative permeability of Iron l i is equal to 181.2157. As mentioned above it is also supposed that e r 51.…”
Section: Antenna Miniaturization Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to enlarge the bandwidth, two popular techniques used, consists of incorporating resonating elements working at nearby frequencies by arranging them on the same plane [14,15] or by using multi layers [16,17] at the expense of a drop in the absorption at certain frequencies in the bandwidth and/or bulkiness. Genetic algorithms [18] and software based optimizations are also used to obtain broadband absorption. However with these methods the physical insight of how absorption is obtained is always debatable.…”
Section: Introductionmentioning
confidence: 99%